PERBANDINGAN PENYERAPAN AIR DAN KUAT TEKAN BETON NORMAL BERLAPIS TERHADAP BETON BERLAPIS DENGAN ABU AMPAS TEBU SEBAGAI BAHAN PENGISI AGREGAT HALUS PADA KAMAR MANDI GEDUNG BERTINGKAT - Rangkuti, Gemala Amira; Dirgantara, Rahmat; Sari, Kartika Indah; Chairina, Ellyza (Universitas Islam Sumatera Utara, 2025)
The abundant availability of bagas seashin North Sumatra open supopport unities for it suseasanenv iron mentally friendly additive incon cretemixtures. This research aims to analyse the effect of bagas seashasapartial replace ment for fine aggregate on the compressive strength hand water absorption of layered concrete for bath room sinmulti-storey buildings. Test objects were made with variation sofbagas seash of 0% (normal), 10%, and 20%, then testedat the ages of 14 and 28 days. There search results showed that at 28 days, the compressive strength of normallayered concrete and concrete with 10% bagas seash was the same, namely 33.33 MPa, where as with the 20% variation it decreased to 30.27 MPa (down 9.18%). Interms of water absorption, layered normal concrete shows the lowest value of 0.65%, while the 10% and 20% mixtures are 0.86% and 0.87% respectively. Thus, the optimum addition of bagas seashis recommended at 10% to maintains table concrete quality.